Do e-athletes move? a study on training and physical exercise in elite e-sports - Kari, T.; Karhulahti, V.-M. (International Journal of Gaming and Computer-Mediated Simulations, 2016)
This article offers possibly the first peer-reviewed study on the training routines of elite e-athletes with special focus on the subjects' physical exercise routines. The study is based on a sample of 115 elite e-athletes. According to the responses, e-athletes train approximately 5.28 hours every day around the year on the elite level. Approximately 1.08 hours of that training is physical exercise. More than half (55.6%) of the elite e-athletes believe that integrating physical exercise in their training programs has a positive effect on esport performance; however, no less than 47.0% of the elite e-athletes do their physical exercise chiefly to maintain overall health. Accordingly, the study indicates that elite e-athletes are active athletes as well, those of age 18 and older exercising physically more than three times the daily 21-minute activity recommendation given by World Health Organization.